Attenuation Of Grass Trimmer Handle Vibration Using Imposing Node Technique - Ko, Ying Hao (2012)
Prolonged use of grass trimmer exposes the user to the risk of hand-arm vibration syndrome. Imposing node technique was investigated in order to achieve low vibration (node) at the grass trimmer handle location. It is established that, for the grass trimmer system which can be modelled as a beam, the vibration at the handle location can be minimized. The mathematical model of grass trimmer system is presented, and a criterion for implementing the vibration attenuation by imposing node technique is developed. The optimum tuning frequencies of tuned vibration absorbers (TVAs) attached at the points of 0.74L and 0.85L along the shaft of grass trimmer were determined using this approach.